THE POSSIBILITY OF USING NON-TRADITIONAL ELEMENTS IN THE EMERGENCY POWER SUPPLY SYSTEM FOR NUCLEAR POWER PLANTS' OWN NEEDS - Y. Demin; I. Sysoev; A. Skomorokhov; V. Ratushny; O. Devitsky (Вестник Северо-Кавказского федерального университета, 2022)
The feature of constructing a power supply system for the mechanisms of own needs of nuclear power plants is reflected. It is noted that the emergency power supply system of power units should provide power supply to consumers in all operating modes of the station, including in the event of loss of working and backup power sources from the power system. The paper shows that thanks to intelligent distribution technologies, the widespread use of distributed generation sources, the NPP's own network can be converted from passive to active. The integration of distributed generation, including renewable distributed generation, changes the flow of energy in the grid from unidirectional to bi-directional. A diagram of the possible application of these devices in the emergency power supply system of a nuclear power plant is proposed. Hybrid hierarchical control is recommended as the most effective method of active control of the emergency power supply system. This will allow widespread use of modern controllers, power electronics for DC / DC, DC / AC conversions and software adapted for small distributed generation.